Pengaruh Pendekatan Berpikir Kausalitik Ber-Scaffolding Tipe 2b Termodifikasi Berbantuan LKS Terhadap Kemampuan Pemecahan Masalah Fluida Dinamis Siswa - Faridatul Helmi; Joni Rokhmat; Jannatin 'Ardhuha (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2017)
This study aims to determine the effect of student worksheet assisted modified causalitic thinking type 2B scaffolding approach toward studentÃ¢â¬â¢s problem solving ability (PSA) in dynamic fluid among second grade student at MAN 1 Mataram in academic year of 2016/2017. This research is a quasi experiment with untreated control design with pretest and posttest. The population in this study were all science students in second grade. The sample was taken by using purposive sampling techniques, which lead XI MIA 3 and XI MIA 1 were chosen as the experimental class and control class, respectively. PSA data collected by essay test that are 4 questions that have been tested for validation and reliability. Homogeneity test, normality test and t test polled varians were used as statistical test. Based on hypothesis test can be concluded that there is the influence of student worksheet assisted modified causalitic thinking type 2B scaffolding approach toward studentÃ¢â¬â¢s PSA in dynamic fluid among second grade student in academic year of 2016/2017.